2022
DOI: 10.3390/polym14173543
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Permittivity Measurement of Ground-Tire Rubber (GTR) during Microwave-Assisted Devulcanization

Abstract: Many efforts are being made to find innovative ways of recycling rubber from end-of-life tires (ELTs), also called ground tire Rubber (GTR). Recycling through devulcanization allows the reintroduction of rubber back into the manufacturing industry. Such a process requires providing enough energy to break the sulfur links, while preventing damage to the polymeric chain. Microwave heating is controllable, efficient, and it does not rely on conventional heating mechanisms (conduction, convection) which may involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…The GTR had an apparent bulk density of 400 kg/m 3 , with granule sizes ranging from 0.5 to 1 mm. The MUT's primary components are as follows [27]: natural rubber (36 %), carbon black (27 %), synthetic rubber (22 %), inorganic components (8.5 %), additives and oil (4.6 %), and sulphur (1.9 %).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The GTR had an apparent bulk density of 400 kg/m 3 , with granule sizes ranging from 0.5 to 1 mm. The MUT's primary components are as follows [27]: natural rubber (36 %), carbon black (27 %), synthetic rubber (22 %), inorganic components (8.5 %), additives and oil (4.6 %), and sulphur (1.9 %).…”
Section: Methodsmentioning
confidence: 99%
“…Samad et al [29] investigated the electrochemical gas sensor response under various conditions and concluded that it could provide a great opportunity to collect high-quality data on air pollutants. Additionally, in [26], three electrochemical sensors were employed to track the VSCs generated during the microwave-assisted devulcanization of GTR in the presence of nitrogen and a small oxygen percentage. When these VSCs were generated during the microwave irradiation, the experimental trials in this study demonstrated that the pyrometer was severely blinded.…”
Section: Sulphur Gas Concentration Monitoringmentioning
confidence: 99%
See 3 more Smart Citations